La encrucijada de AMLO: entre la soberanía energética y la acción climática - Martínez, Nain (El Colegio de México A.C., 2025)
This study examines how President López Obrador’s (AMLO) energy policy–centered on “energy sovereignty” through strengthening the Federal Electricity Commission (CFE)–collided with Mexico’s national climate mitigation targets and the shift toward renewables. Using political economy analysis, the article traces government decisions, opposition from companies and NGOs, and external influences from both the Trump and Biden administrations and the USMCA. The government’s reorientation marginalized the renewable sector, triggering litigation and creating a climate policy vacuum. International pressure, particularly from the Biden administration, along with domestic opposition prompted policy adjustments after 2021, though fundamental contradictions persisted. The findings reveal a rise in GHG emissions, underscoring the urgency of rethinking energy sovereignty within the global climate crisis. Thus, the Mexican case demonstrates that left-wing governments may adopt divergent strategies for the energy transition, shaped by historical, institutional, and geopolitical factors. The study concludes by highlighting the need for policies that integrate the expansion of clean energies as a key component of energy self-sufficiency and security, thereby transcending the false dichotomy between state control of fossil fuels and a free-market approach to renewables.